Dispersal and edge behaviour of bark beetles and predators inhabiting red pine plantations. (12th August 2012) - Costa, Arnaud; A, Min; Boone, Celia K.; Kendrick, Alexander P.; Murphy, Robert J.; Sharpee, William C.; Raffa, Kenneth F.; Reeve, John D.
Abstract : 1 Quantifying dispersal in predator–prey systems can improve our understanding of how these species interact in space and time, as well as their relative distributions across complex landscapes. 2 We measured the dispersal abilities of three forest insects associated with red pine decline: the eastern five spined pine engraver Ips grandicollis (Coleoptera: Curculionidae), its main predator Thanasimus dubius (Coleoptera: Cleridae) and the basal stem and root colonizer Dendroctonus valens (Coleoptera: Curculionidae). We also examined the edge behaviours of these species and the predator Platysoma spp (Coleoptera: Histeridae) between red pine stands (habitat) and clearings (nonhabitat). 3 Thanasimus dubius dispersed 12 times farther than its prey I. grandicollis, with 50% of predators dispersing farther than 1.54 km. This profound difference in dispersal behaviour between prey and predator may contribute to the clumped distribution of I. grandicollis . 4 Most T. dubius and D. valens were confined in the pine forest, thus showing strong edge behaviour. This differed from I. grandicollis and Platysoma spp., which were commonly found in open areas adjacent to red pine plantations. 5 The bark beetle I. grandicollis and one of its main predators, T. dubius, exhibited different patterns of movement within a fragmented landscape. Despite a greater dispersal ability of T. dubius within forests, the spatial distribution of this predator may be restricted by fragmentation of its habitat, and provide an opportunity for partial escape of its prey. 6 The present study contributes to our knowledge of top‐down forces within red pine stands undergoing decline. Differences of dispersal patterns and edge behaviour could contribute to the initiation of new pockets of decline, as well as the connectedness among existing ones.